2016
DOI: 10.1186/s13099-016-0149-6
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of resistant starch and wheat bran consumption on enteric inflammation in relation to colonic bacterial community structures and short-chain fatty acid concentrations in mice

Abstract: Background: Identifying the connection among diet, the intestinal microbiome, and host health is currently an area of intensive research, but the potential of dietary fiber (DF) consumption to ameliorate intestinal inflammation has not been extensively studied. We examined the impacts of the DFs, wheat bran (WB) and resistant starch (RS) on host enteric health. A murine model of acute Th1/Th17 colitis (i.e. incited by Citrobacter rodentium) was used.Results: Diets enriched with RS increased weight gain in mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 93 publications
(115 reference statements)
2
42
0
3
Order By: Relevance
“…Nofrarías et al (15) found that long-term intake of 25 or 35 % RPS could increase butyrate production and improve colonic mucosal integrity in pigs. In accordance, several studies have shown that mouse or rat diets supplemented with RS could promote gut health, which is likely attributable to an alteration in the microbial community characterised by increased butyrateproducing bacteria, thereby reducing inflammation and maintaining physiologic balance (17) . Moreover, Keenan et al (18) found that rats fed RS had increased gene transcription of proglucagon (Gcg) in the caecum.…”
mentioning
confidence: 65%
“…Nofrarías et al (15) found that long-term intake of 25 or 35 % RPS could increase butyrate production and improve colonic mucosal integrity in pigs. In accordance, several studies have shown that mouse or rat diets supplemented with RS could promote gut health, which is likely attributable to an alteration in the microbial community characterised by increased butyrateproducing bacteria, thereby reducing inflammation and maintaining physiologic balance (17) . Moreover, Keenan et al (18) found that rats fed RS had increased gene transcription of proglucagon (Gcg) in the caecum.…”
mentioning
confidence: 65%
“…The concentrations of SCFA, including acetate, propionate and butyrate in intestinal tract increased in varying degrees after extra addition of slowly digested carbohydrates in daily diets, such as resistant starch, 39) guar gum, 40) pectin, 41) inulin 42) and so on. In this study, acarbose and voglibose significantly increased butyrate concentration (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6. Using sterile iris scissors and forceps, conduct a midline laparotomy to exteriorize the intestine (Jiminez, Uwiera, Abbott, Uwiera, & Inglis, 2016).…”
Section: Of 22mentioning
confidence: 99%